Síndrome del intestino irritable y estrés académico en estudiantes de la carrera de Medicina de la Universidad Nacional de Loja - Pacheco Tapia, Jhesua David (2021)
The irritable bowel syndrome, IBS is a chronic and recurring gastrointestinal disorder, nowadays it is frequently diagnosed to young people mostly. It is characterized by an ache or belly pain, besides some changes of bowel movement stool; the current research paper was made knowing that the psychological component is the main factor joined to that disorder with the goal of determining the irritable bowel syndrome linked to academic stress among the medicine students of the National University of Loja during October 2019 – March 2020 academic year. The analysis was descriptive, cross section, correlative; 229 medicine students participated and a survey was asked for them, that survey included: SISCO inventory to establish the academic stress rate and 6 questions to determine if irritable bowel syndrome Roma IV criteria is ranked. The irritable bowel syndrome frequency was 19,21% (44 cases); on the other hand, 93,45% (214 cases) showed some academic stress level but the moderated stress is in a higher level, 69.43% . The research determined that the most amount of irritable bowel syndrome is among academic stress participants, 19.63% as opposed to 13.33% who didn´t show stress, however, this relation wasn´t statistically significant (X2 0,357; p 0,549 > p 0,05); so, there wasn´t any relation between the irritable bowel syndrome and academic stress. Key words: Constipation, Roma criteria, diarrhea, belly pain.